Effect of various factors influencing the generation of hemispherical micro features using non-conformal RMEDM. Issue 2 (November 2019) - Roy, T.; Balasubramaniam, R.
Abstract: Non-conformal reverse micro electrical discharge machining (NC-RMEDM) is a variant of conventional RMEDM developed by the present authors wherein modification in the tool is carried out to generate different shapes of micro features. In this study, the effect of various factors like flat bottom and taper bottom hole, inversing the position of tool and workpiece and changing the hole depth have been experimentally investigated to determine the optimal combination required for generating hemispherical shaped micro features. It was found that hemispherical shaped micro feature can be generated by employing tapered bottom blind hole as tool. Buoyancy assisted machining (BAM) with traverse of workpiece (anode) downwards into the tool (cathode) and vice versa, i.e., buoyancy opposed machining (BOM) with traverse of tool downwards into the workpiece were carried out to study the generation of hemispherical micro feature based on inversion of electrode positions. Although both BAM and BOM generated hemispherical shaped feature, BAM is preferred due to reduced machining time as opposed to BOM. Also, increasing the hole depths led to altering the shape of micro feature from hemispherical to cylindrical with hemispherical end and coni-spherical end. An array of hemispherical micro features was fabricated based on the finding from this study, and surface roughness analysis was carried out which showed that irrespective of the position of micro feature on the array, surface roughness at the tip and base of the micro feature is lower as compared to side portion.